Acetylcholinesterase inhibitory and antioxidant properties of Ampelocissus sp. (Isi Nyaru) extract / Rosniyati Omar - Rosniyati , Omar (2018)
Ampelocissus sp. (Isi Nyaru) is a genus of Vitaceae has been used in traditional medicine for the treatment of inflammation in tissue damage, bruises and after childbirth. Alzheimer’s disease (AD) is neurodegenerative disease characterized by deficiency in more than an area of cognition which involving mood and behavior changes, sporadic memory, language, and attention. In this study the antioxidant and acetylcholinesterase (AChE) inhibitory activity of Ampelocissus sp. extract was evaluated. The chemical compounds of Ampelocissus sp. were separated by thin layer chromatography (TLC) and detected with Vanillin-sulphuric and Dragendroff’s spray reagent. Saponin, alkaloids, terpenoids and flavonoids were detected in the extracts. The phytochemical compounds were analyzed using Liquid Chromatography Mass Spectrometry tandem with Mass Spectrometry (LCMS/MS). The methanol aqueous extract showed the presence of 12 compounds namely 5-aminopentanoic acid, 11-amino-undecanoic acid, C16 sphinganine, (+)-eudesmin, his lys cys, lys his met, his met lys, ethephon, L-arginine, sulpho NONOate, gln gln trp and dichloroacetate5-aminopentanoic acid, 11-amino-undecanoic acid, C16 sphinganine, (+)-eudesmin, his lys cys, lys his met, his met lys, ethephon, L-arginine, sulpho NONOate, gln gln trp and dichloroacetate. The highest content of phenol and flavonoids were detected in chloroform extracts at 0.42 ± 0.012 mg GAE/g and 2.007 ± 0.001 mg QE/g, respectively. The ethyl acetate extract showed the highest DPPH scavenging activity at IC50 1.49 mg/ml, highest metal chelating activity at IC50 0.07 mg/ml. Meanwhile chloroform extract showed the highest reducing power at 6.03 mmol Fe+/g in FRAP, highest IC50 0.49 mg/ml in NORSA and the highest superoxide radical scavenging activity at 26.8 %. Among 17 compounds isolated from TLC plates of Ampelocissus sp. the highest percentage of AChE inhibition activity was shown by methanol aqueous extract at 55.56%. Thus, the findings of this research showed that the extract of Ampelocissus sp. possessed good antioxidant activity and AChE inhibitors potential to be used for AD treatment.